Advances in High-Z semiconductor radiation detectors at BNL - Pinaroli, G.; Bolotnikov, A. E.; Bouckicha, M.; Capocasa, F.; Cultrera, L.; Rumaiz, A. K.; Tamura, E.; Carini, G. A. (Frontiers in Detector Science and Technology, 2025)
Semiconductor radiation detectors play a crucial role in scientific research and technological applications, with materials typically categorized as low- or high-Z depending on their atomic numbers and densities. This distinction is not strictly defined because the selection of materials depends on the specific application and the energy range. Low-Z semiconductors such as diamond, silicon (Si), selenium (Se), and silicon carbide (SiC) are widely used in X-ray and charged particle detection due to their excellent charge transport properties and radiation hardness. High-Z semiconductors, including germanium (Ge) and compound materials such as cadmium telluride (CdTe), cadmium zinc telluride (CdZnTe or CZT), and emerging lead halide perovskites (most promising is CsPbBr3), offer absorption efficiency in the hard X-ray and gamma-ray regions comparable to CZT. These materials enable advancements in diverse fields, including biology, astrophysics, medical imaging, and industrial inspection. At Brookhaven National Laboratory (BNL), the Instrumentation Department is at the forefront of developing cutting-edge semiconductor detector technologies to address the evolving needs of fundamental and applied research. The projects cover the entire development cycle, from the investigation of new materials and optimization of detector architectures to the design of low-noise readout electronics and signal processing techniques. The ongoing research projects focus on next-generation detection systems that improve sensitivity, energy resolution, and robustness for a wide range of applications. The continuous demand for versatile and high-performance detector systems drives research in multiple directions with emphasis on advancing detector integration within complex experimental requirements, ensuring seamless compatibility with large-scale scientific facilities, and developing scalable and cost-effective fabrication techniques. The combination of novel materials, innovative detector designs, and state-of-the-art readout electronics paves the way for next-generation semiconductor detectors with unprecedented performance. In this work, we present an overview of our recent advances in semiconductor detectors and their applications.